Monitoring and evaluation of free acidity levels in Talh honey originated from Talh tree Acacia gerrardii Benth - Hael S.A. Raweh (Elsevier, 2022)
Talh, Acacia gerrardii Benth. (Talh relevant to the Arabic local name) trees are main nectar source for honey production in the Arabian Peninsula. However, honey originated from nectar of this plant is characterized by relatively high levels of free acidity (FA), which has caused quality concerns with regard to marketing and exportation of Talh honey. This pioneer study investigated the free acidity of Talh honey starting where the honey originates and continuing throughout its processing and preparation. Furthermore, the pH and electrical conductivity (EC) of tested Talh honey made by Apis mellifera L. were monitored. Samples were collected during the flowering season of Talh trees. The FA levels showed a gradual significant increase from Talh tree leaves and flowers (30 ± 0.99; 34 ± 0.92 meq/kg) to bee crop (honey stomach) and unripe honey (43 ± 1.80; 72 ± 1.56 meq/kg) and finally to ripe honey (77 ± 1.28 meq/kg), respectively. For the pH level, the highest value was recorded in the leaves (6.41 ± 0.03), and it decreased as honey production continued, reaching its lowest value in ripe honey (4.91 ± 0.06). Contrarily, the EC increased from 0.98 ± 0.06 mS/cm in the leaves to 1.56 ± 0.08 mS/cm in unripe honey. Seasonal variations in FA, pH, and EC were monitored, and these factors showed significant fluctuations over time during the experimental period. The mean values of FA, pH, and EC in the newly harvested Talh honey were 82 meq/kg, 5.1, and 1.54 mS/cm, respectively. The levels of FA in Talh honey were higher than the range permitted in the international standards for honey quality. FA was significantly positive correlated with relative humidity (RH) and EC, whereas a significant negative correlation was observed between FA and pH. These results confirmed that Talh honey is primitively highly acidic, with low pH and high EC. The high levels of FA in the Talh honey were related to the nature of the origin plant, and were not associated with honey quality. The modification of Talh honey standards based on regional honey characteristics are suggested. Further research on the physicochemical properties of all Acacia spp. honeys that appear to have high FA levels is recommended.